SELEKSI INDUK JANTAN CUPANG ALAM B CHANNOIDES DAN PENENTUAN UMUR PANEN LARVA METODE PENGOCOKAN SERTA EFEKTIFITASNYA - Agus Priyadi; Asep Permana; Ahmad Musa; Bastiar Nur; Sawung Cindelaras; Sulasy Rohmy; Siti Zuhriyyah Musthofa (Universitas Sriwijaya, 2021)
Snakehead (Betta channoides) is a native and endemic fish from East Kalimantan. It has a beautiful and attractive color as an ornamental fish commodity. This fish is incubating her eggs in its mouth or a mouthbrooder. The important thing in spawning is male brood selection, it is related to eggs incubating and also proper harvests time and technique in order to maximize the result. The aim of this research is to determine the criteria for good male broodstock used in spawning, proper time to harvest the larvae and the effectiveness of shaking technique to harvest the larvae. There are two criteria selecting male broodstock, 1. Mouth shape and 2. Body coloration. Determination of harvest time was carried by harvesting larvae 4th, 8th and 12th day after spawning. The effectiveness of shaking technique was seen by comparing with broodstock natural larva released. The parameters that observed in this research were the shape of male broodstock, male body color, the number of harvested larvae and harvesting time between shaking technique and naturally released by male. The result showed that selection of male snakehead betta good for spawning was the male broodstock with wider mouth shape and have width of 0.5cm also with not too bright red body coloration. The proper harvesting time for maximum yield was the 8th day after spawning. The shaking technique in harvesting is more effective in harvest time, number of larvae, survival rate of larvae and its simplicity comparing to natural released by broodstock. Keywords: selection, male broodstock, larva harvest, shaking, B. channoides